Post-radiation Plasma Epstein-Barr Virus DNA and Local Clinical Remission After Radical Intensity-modulated Radiation Therapy for Nasopharyngeal Carcinoma. Issue 1 (January 2016) - Lee, V.H.F.; Kwong, D.L.W.; Leung, T.W.; Choi, C.W.; Lam, K.O.; Sze, C.K.; Ho, P.; Chan, W.L.; Wong, L.S.; Leung, D.
Abstract: Aims: We studied if post-radiation plasma Epstein-Barr virus (EBV) DNA predicted local clinical remission after radical intensity-modulated radiation therapy (IMRT) for nasopharyngeal carcinoma. Materials and methods: Patients with non-metastatic nasopharyngeal carcinoma with baseline and serial plasma EBV DNA were treated with radical IMRT ± adjunct chemotherapy. Eight weeks after IMRT, they had plasma EBV DNA and routine six-site random nasopharyngeal biopsies on the same day. A repeat biopsy was carried out every 2 weeks if residual tumours were noted in previous biopsies until 12 weeks after IMRT when local persistence was defined. Correlation of undetectable plasma EBV DNA with local clinical remission was carried out. Results: Two hundred and sixty patients with serial plasma EBV DNA completed IMRT, after a median follow-up of 3.1 years. Only one (0.4%) suffered from local persistence. Area under the curve values of receiver operating characteristics of undetectable plasma EBV DNA for negative biopsy at 8 weeks and local persistence were 0.642 and 0.439, respectively. They increased to 0.856 ( P = 0.007) and 0.952 ( P = 0.119), respectively, when combined with age <65 years and T1/T2 stage. Conclusions: Post-treatment plasma EBV DNA was not useful to predict local clinical remission in this study, probably because of excellent local control after IMRT. However, it may serve as a reference for high-risk patients treated with older radiation techniques. Highlights: Correlated post-radiation plasma EBV DNA with local remission after IMRT for NPC. In total, 260 patients had their post-radiation plasma EBV DNA taken at 8 weeks after IMRT. Results showed excellent outcomes with only one local persistence after IMRT. Plasma EBV DNA was minimally predictive of local remission due to lack of events. It may serve as a reference for patients treated with older radiation techniques.